Analisis Faktor Penyebab Pending Klaim Rawat Inap Bpjs Kesehatan di Rumah Sakit Efarina Pangkalan Kerinci Riau - Riri Handayani; Alih Germas Kodyat; Aliefety Putu Garnida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the factors causing pending BPJS Kesehatan inpatient claims at Efarina Hospital, Pangkalan Kerinci, Riau, in 2024. Pending claims are a significant obstacle in the hospital financing system because they impact cash flow, service efficiency, and operational sustainability. The study used a mixed method (quantitative and qualitative) design. The research sample consisted of 1,278 pending inpatient claim files and interviews using the matrix triangulation technique, Focus Group Discussion (FGD) related to the claims process. Data were collected through document review, in-depth interviews, and observation of the administrative process. The results showed that the dominant factors causing pending claims were incomplete medical resumes (56.73%), inaccurate coding (34.66%), and incomplete claim files (8.61%). The impact of pending claims was quite significant, namely delays in receiving payments from BPJS Kesehatan and increased hospital operational costs. This study recommends strengthening the claims management system through improving the accuracy of medical records, regular training, optimizing information technology, and stricter internal supervision. In conclusion, improvement efforts focused on human resources, administration, and digital systems are crucial for reducing the number of pending claims, enabling hospitals to improve efficiency, regulatory compliance, and the quality of healthcare services.